Renal Histomorphological Effects of Vonoprazan Vs Omeprazole: A Comparative Study in Rats - Hamid, Kanza; Qamar, Abdullah; Khan, Muhammad Marghoob; Waseem, Naureen; Raja, Hira; Akhtar, Mahmood (Journal of Rawalpindi Medical College, 2025)
Objective: This research aimed to assess and compare the nephrotoxicity of omeprazole and vonoprazan on the basis of gross and histomorphological parameters in experimental rats. Methods: This laboratory-based randomized controlled trial included 60 male Sprague Dawley rats (250 ± 50 g), randomly allocated into three groups: control (Group A), omeprazole-treated (Group B, 20 mg/kg/day), and vonoprazan-treated (Group C, 10 mg/kg/day). Drugs were administered orally for six weeks. Following euthanasia, kidneys were excised, weighed, and prepared for microscopic analysis using hematoxylin and eosin (H&E) and Masson’s trichrome stains. Data analysis was done using SPSS 26, with statistical significance set at p < 0.05. Results: Omeprazole-treated rats exhibited significant reductions in glomerular diameter (23.5 ± 1.9 µm vs. 37.9 ± 1.3 µm in controls, p < 0.000), kidney weight (0.92 ± 0.12 g vs. 1.39 ± 0.09 g, p < 0.000), and relative tissue body weight index (RTBWI) (0.37 ± 0.06 vs. 0.50 ± 0.04, p < 0.000). The vonoprazan-treated rats showed relatively normal renal morphology with fewer histological changes and non-significant changes in renal parameters as compared to controls. Conclusion: Omeprazole-induced nephrotoxicity was manifested as histopathological injury and deranged renal function parameters. Vonoprazan, on the other hand, showed a comparatively safer renal profile and indicated it to be an ideal nephroprotective drug alternative to proton pump inhibitors. Further studies are required to validate such findings and elucidate the mechanisms behind them.